Identifying the Components and Dimensions of an Operational Strategy Model Based on the Realization of Social Banking with an Approach to Social Responsibility, Green Banking, and Banking via Social Networks in Parsian Bank - Khaki , Neda; Mohammadi Nasab, Mahdi; Sanavi Fard, Rasoul (Management Strategies and Engineering Sciences, 2026)
This study aimed to identify and model the operational components and dimensions of social banking based on social responsibility, green banking, and social media-based banking within Parsian Bank to enhance sustainable development and institutional accountability. The research employed a qualitative grounded theory design to explore and conceptualize the dimensions of social banking. The statistical population included two expert groups: banking specialists and academic scholars. Using purposive judgmental sampling, ten participants were selected from Parsian Bank branches in Tehran and Karaj and relevant academic institutions. Semi-structured, in-depth interviews were conducted until theoretical saturation was achieved. The data were analyzed through open, axial, and selective coding, with triangulation and expert validation ensuring credibility. Intercoder reliability reached 75.75%, and the kappa coefficient of 0.821 confirmed coding consistency. The analysis revealed six main clusters: influential factors, core categories, outcomes, strategies, context, and intervening factors. Core categories included three foundational dimensions—social responsibility-based banking, green banking, and social media-driven banking—supported by key contextual factors such as digital transformation, governance policies, and social capital. The model demonstrated that integrating social responsibility and green practices within a digitally enabled framework significantly enhances customer loyalty, trust, and sustainable development. The findings confirmed that effective social banking requires regulatory clarity, cultural adaptability, and employee awareness, aligning with sustainability-oriented banking paradigms. The study presents a comprehensive operational strategy model demonstrating that the convergence of social responsibility, environmental stewardship, and digital transformation strengthens organizational resilience and customer trust. By embedding CSR, green finance, and technological innovation into banking operations, institutions can achieve long-term sustainability and competitive advantage.